On the effect of microstructural changes of blood on energy dissipation in Couette flow - Kaliviotis, Efstathios; Yianneskis, Michael (My University, 2008)
Red blood cell aggregation affects the flow of blood at low shear rates; not only the behaviour of the fluid deviates from its Newtonian characteristics, but, depending on the shearing history of the flow, the non-Newtonian characteristics may be influenced. It is not clear how the time and flow-dependent characteristics of the microstructural network developed in blood affect its mechanical properties. The present study aims to improve understanding of the effect of dynamic flow conditions on microstructural characteristics and consequently on the mechanical properties of the fluid. Viscosity measurements on blood samples from healthy volunteers (H=0.45) were taken with a double-walled Couette rheometric cell, under unsteady and quasi-unsteady flow conditions. The aggregation extent index A α, and the microstructural integrity index AI were assessed with an optical shearing system and image analysis. Results showed that energy losses in Couette geometries may depend on the structural integrity of the developed RBC network. © 2008 - IOS Press and the authors. All rights reserved.
Keywords: Microstructural integrity; RBC aggregation; Shear rate variation with time